Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.12911/22998993/74288
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Water Quality in a Water Supply Network

Abstract: An effect of factors determining water quality in the water supply network in Kraków is assessed. The data collected over a four-year research period included quality parameters of water taken from the water distribution system in the period between 1 January 2011 and 31 December 2014. In the analysis the supply zones of four municipal water treatment plants in Krakow were considered. The selection of 29 water sampling points within the supply area allowed comparing water quality with respect to operational an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…For instance, changes in color of water in distribution networks could occur due to the release of iron in iron-based pipes (Vreeburg & Boxall 2007), implying that the type of pipe material in the network could influence water discoloration and associated chemical parameters. Moreover, studies have shown that changes in the concentrations of iron in water could induce changes in pH, alkalinity, and electrical conductivity (Bergel et al 2013;Jachimowski 2017). However, the results of the random forest models suggest that pipe material has the least impact on the physical-chemical parameters of water quality included in this study.…”
Section: Conditional Probabilities Of Posterior Predictionsmentioning
confidence: 71%
“…For instance, changes in color of water in distribution networks could occur due to the release of iron in iron-based pipes (Vreeburg & Boxall 2007), implying that the type of pipe material in the network could influence water discoloration and associated chemical parameters. Moreover, studies have shown that changes in the concentrations of iron in water could induce changes in pH, alkalinity, and electrical conductivity (Bergel et al 2013;Jachimowski 2017). However, the results of the random forest models suggest that pipe material has the least impact on the physical-chemical parameters of water quality included in this study.…”
Section: Conditional Probabilities Of Posterior Predictionsmentioning
confidence: 71%
“…Drinking water supply systems are commonly affected by the raw water quality and the capacity of the treatment process to remove pollutants. The biological and physicochemical stability of the water in the network is also a quality issue, as secondary contamination of the water can occur in the supply networks [41]. Among these factors, the effectiveness of the treatment process is certainly the most important and must be carefully adapted to the quality of the incoming raw water.…”
Section: Discussionmentioning
confidence: 99%
“…Such seasonal variations in drinking water system performance were potentially due to rapid changes in raw water quality as a result of precipitation (e.g. increased stormwater flows and discharges, soil erosion, sporadic high turbidity) and an increased microbial load entering drinking water distribution [41] (e.g. overloading of the treatment process, adversely affecting disinfection efficiency) [17,42,43].…”
Section: Drinking Water Quality Issuesmentioning
confidence: 99%